Effect of urine, poultry manure, and dewatered faecal sludge on agronomic characteristics of cabbage in Accra, Ghana - Amoah, Philip; Adamtey, N.; Cofie, Olufunke O. (MDPI, 2017)
The study was to assess the: (i) effect of human urine and other organic inputs on cabbage growth, yield, nutrient uptake, N-use efficiency, and soil chemical characteristics; (ii) economic returns of the use of urine and/or other organic inputs as a source of fertiliser for cabbage production. To meet these objectives, participatory field trials were conducted at Dzorwulu, Accra. Four different treatments (Urine alone, Urine + dewatered faecal sludge (DFS), Urine + poultry droppings (PD), NPK (15-15-15) + PD) were applied in a Randomised Complete Block Design (RCBD) with soil alone as control. Each treatment was applied at a rate of 121 kg·N·ha−1 corresponding to the Nitrogen requirement of cabbage in Ghana. Growth and yield parameters, plant nutrient uptake, and soil chemical characteristics were determined using standard protocols. There were no significant differences between treatments for cabbage head weight, or total and marketable yields. However, unmarketable yield from NPK + PD was 1 to 2 times higher (p < 0.05) than those from Urine + PD, Urine + DFS, and Urine alone. Seasonal effect on yields was also pronounced with higher (p < 0.001) cabbage head weight (0.95 kg) and marketable yields (12.7 kg·ha−1) in the dry season than the rainy season (0.42 kg and 6.27 kg·ha−1). There was higher (p < 0.005) phosphorous uptake in cabbage from Urine + PD treated soil than those from other treatments. Nitrogen (N), phosphorous (P), and potassium (K) uptake in the dry season was significantly higher than the rainy season. Soils treated with Urine + DFS and Urine + PD were high in total N content. Urine + PD and Urine + DFS treated soils gave fairly high yield than PD + NPK with a net gain of US$1452.0 and US$1663.5, respectively. The application of urine in combination with poultry droppings has the potential to improve cabbage yields, nutrient uptake, and soil nitrogen and phosphorous content.